Engineering And Construction Problems in The Field Of Preservation And Protection Of Historical Buildings (Texas Journal of Engineering and Technology, 2024)
Engineering and construction problems in the field of protection of historical and ancient buildings are not few and often they are very complex. In the article, the tasks of permanent protection of buildings are aimed at solving in the general situation, various methods of temporary and permanent protection in the restoration practice, issues about the efficiency of building protection works are reflected in the article.